ISTEM INFORMASI PEMAKAIAN DAN PENGORDERAN CHEMICAL PT. AGRICON PUTRA CITRA OPTIMA (TERMINIX) BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract Currently  mobile  devices  such  as  HP  and  tablets  have  become  the  basic  human  needs. Advantages  of mobile devices  that  can be accessed anywhere  and  anytime  is one reason  people use it. With this trend, web-based applications to mobile will be a key option. System information about the cost of maintenance of the ground is one of the applications that can be accessed through mobile devices.The purpose of this is to make an application penetilian usage and chemical ordering in PT. Agricon Putra Citra Optima (Terminix) Based Android, where technicians can easily orderer chemical in any placeAnd  goals for  the  office  itself  is  easier for  administrators  to  create a  monthly report.  It also  allows  administrators  and  technicians  in  view  of  the  stock  of  chemicals  in  the  warehouse.Keywords: mobile, systems, technicians, admin